'National Hero and Very Queer Fish': Empire, Sexuality and the British Remembrance of General Gordon, 1918–72. (13th October 2014) - Jones, Max
Abstract : This article presents the first detailed study of General Gordon's remembrance in Britain between 1918 and 1972. Previous scholars have exaggerated the impact of Lytton Strachey's Eminent Victorians (1918). Strachey damaged Gordon's reputation, but part one reveals how several commentators forcefully rebutted Eminent Victorians ; official commemorations, books, radio plays, and films celebrated Gordon in the 1930s, as empire featured prominently in mass culture. Didactic uses of his example by the state diminished after 1945, but parts 2 and 3 show how writers used Gordon's story to engage with new debates about Britain's role in the world, immigration and sexuality. The article reveals how a fascination with the sexuality of heroes inspired men as diverse as Viscount Robin Maugham and East End gangster Ronnie Kray to identify with Gordon. Maugham's works and the feature film Khartoum (1966) expressed nostalgia for empire during decolonization, but American screenwriter Robert Ardrey also drew on his experiences in the Congo to present a dark vision of African savagery in Khartoum, a vision performed at Pinewood studios by black immigrants from London's slums. The article questions Edward Berenson's emphasis on the 'charismatic aura' of heroes, emphasizing instead the diversity of engagements inspired through different genre.